Quality of life in patients with spinal muscular atrophy in Brazil: patient self-assessment and carer perception - Maíra Coelho; Marise Bueno Zonta; Salmo Raskin; Silvia Valderramas (Revista Paulista de Pediatria)
ABSTRACT Objectives: The aim of this study was to assess the perception of quality of life of patients with spinal muscular atrophy (SMA) and investigate whether there is a correlation between patients’ perception and that of their carers. Methods: Cross-sectional analytical observational study. In the first part, socioeconomic, demographic, clinical, and treatment information were collected from patients diagnosed with SMA, regardless of type, sex, or age. SMA type 1 does not sit; SMA type 2 sits; SMA type 3 walks; and SMA type 4 begins in adulthood. In the second part of the study, patients aged between 2 and 25 years and their caregivers responded to the Pediatric Quality of Life Inventory 4.0 questionnaire. Results: Of the 235 families recruited, 167 were eligible to respond to the questionnaire, 115 caregivers and 49 patients were included. The results point to a different perception of quality of life between patients and caregivers. Patients with SMA type 2 perceive more impaired physical and emotional capacity compared to SMA type 3 and 1, respectively. As for caregivers, the perception of quality of life in relation to physical and social capacity and the total score are worse for patients with SMA type 1 compared to other types. Perceptions correlate with emotional capacity in SMA type 2 and the total aspect in SMA type 3. Conclusions: Patients with SMA type 2 had a worse perception of their quality of life than other patients. Perception differed between patients and their caregivers, with the former having a better perception than the latter.